2018
DOI: 10.1113/ep086654
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic response to incremental increases in negative intrathoracic pressure in healthy humans

Abstract: Negative intrathoracic pressure (nITP) generally augments venous return and left ventricular (LV) stroke volume (LVSV), though large increases in nITP, commonly seen in respiratory disease, attenuate LVSV. Despite this consistent finding, the degree of nITP required to reduce LVSV and the contributions of series and direct ventricular interaction (DVI) in mediating this response remain unclear. We hypothesized that nITP ≤-15 cmH O would augment LVSV, while nITP ≥-20 cmH O would reduce LVSV via DVI and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
0
11
3
Order By: Relevance
“…We speculate that the lower P oes induced by the recruitment of the inspiratory rib cage muscles in RC caused a greater accumulation of blood into the highly compliant pulmonary vasculature compared to AB and SP (Flamm et al., 1990). In support, others showed that inspiratory loading eliciting end‐inspiratory P oes below −20 cmH 2 O resulted in greater right ventricular filling, as evidenced by an increase in the radius of the septal curvature (Cheyne et al., 2018). Interestingly, this led to a decrease in left ventricular filling by direct ventricular interaction, indicated by the decrease in left ventricular SV (Cheyne et al., 2016, 2018).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We speculate that the lower P oes induced by the recruitment of the inspiratory rib cage muscles in RC caused a greater accumulation of blood into the highly compliant pulmonary vasculature compared to AB and SP (Flamm et al., 1990). In support, others showed that inspiratory loading eliciting end‐inspiratory P oes below −20 cmH 2 O resulted in greater right ventricular filling, as evidenced by an increase in the radius of the septal curvature (Cheyne et al., 2018). Interestingly, this led to a decrease in left ventricular filling by direct ventricular interaction, indicated by the decrease in left ventricular SV (Cheyne et al., 2016, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…In support, others showed that inspiratory loading eliciting end‐inspiratory P oes below −20 cmH 2 O resulted in greater right ventricular filling, as evidenced by an increase in the radius of the septal curvature (Cheyne et al., 2018). Interestingly, this led to a decrease in left ventricular filling by direct ventricular interaction, indicated by the decrease in left ventricular SV (Cheyne et al., 2016, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…As such, the impact of breathing through additional resistances as described in this review paper are in addition to this intrinsic resistance. Contrary to observations that indicate a positive influence of reduced ITP on cardiac function and circulation, there are other reports that large reductions in ITP (i.e., Ͼ20 cmH 2 O) have resulted in adverse hemodynamic effects such as increased left ventricular transmural pressure gradient or afterload (37,64,69), limited flow in the inferior vena cava (9,40,55), reduced cardiac filling (8), compromised left ventricular geometry and function (35), and lower stroke volume (7,8,80). The latter observations are associated with the physiology of individuals who create large negative "swings" in ITP during inspiration such as healthy subjects performing a sustained Mueller maneuver (5,68,69,76,77) or the pathophysiology of patients with heart failure, chronic obstructive lung disease, and asthma (5,43,58,67).…”
Section: Techniques For Study Of the Respiratory Pump On Hemodynamicsmentioning
confidence: 84%
“…This study was designed and performed as an independent study but used the same subjects as a previous investigation (16). Subjects (11 men and 12 women) were 22 Ϯ 2 yr old with a body mass index of 22.4 Ϯ 2.2 kg/m 2 , forced vital capacity of 4.83 Ϯ 0.87 l [104 Ϯ 7%predicted (%pred)], forced expiratory volume in 1 s of 4.00 Ϯ 0.68 l (101 Ϯ 8%pred), total lung capacity of 5.99 Ϯ 1.00 l (97 Ϯ 7%pred), residual volume/total lung capacity of 23 Ϯ 6% (96 Ϯ 23%pred), and IC of 3.08 Ϯ 0.62 l (100 Ϯ 14%pred).…”
Section: Resultsmentioning
confidence: 99%